2022
DOI: 10.3389/fonc.2022.814667
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Deep Learning-Based Automated Detection of Primary Spine Tumors on MRI Using the Turing Test

Abstract: BackgroundRecently, the Turing test has been used to investigate whether machines have intelligence similar to humans. Our study aimed to assess the ability of an artificial intelligence (AI) system for spine tumor detection using the Turing test.MethodsOur retrospective study data included 12179 images from 321 patients for developing AI detection systems and 6635 images from 187 patients for the Turing test. We utilized a deep learning-based tumor detection system with Faster R-CNN architecture, which genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Some researchers have reported that artificial intelligence (AI) models aid in the diagnosis of spinal tumors. 5 , 6 , 7 , 8 , 9 Automated object detection and segmentation of spinal tumors yielded a high accuracy that was comparable to that of the physicians. 6 , 7 , 9 Besides these, classification models of spinal tumors have been established 8 and one of them was a model to discriminate between schwannomas and meningiomas.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Some researchers have reported that artificial intelligence (AI) models aid in the diagnosis of spinal tumors. 5 , 6 , 7 , 8 , 9 Automated object detection and segmentation of spinal tumors yielded a high accuracy that was comparable to that of the physicians. 6 , 7 , 9 Besides these, classification models of spinal tumors have been established 8 and one of them was a model to discriminate between schwannomas and meningiomas.…”
Section: Introductionmentioning
confidence: 80%
“… 5 , 6 , 7 , 8 , 9 Automated object detection and segmentation of spinal tumors yielded a high accuracy that was comparable to that of the physicians. 6 , 7 , 9 Besides these, classification models of spinal tumors have been established 8 and one of them was a model to discriminate between schwannomas and meningiomas. 5 In this study, magnetic resonance imaging (MRI) of 84 patients was analyzed, and the area under the receiver-operating characteristic curve (AUROC) was 0.88.…”
Section: Introductionmentioning
confidence: 80%
“…Several works consider deep learning models for detection of abnormalities in the spinal column. In [26], authors propose a study the performances of a Faster R-CNN network on MRI images. In [27] authors exploit Siamese networks to detect spine metastases from MRI images.…”
Section: A Related Workmentioning
confidence: 99%
“…[19] Several researchers have proposed an automated DL framework based on an ensemble of U-Nets to perform vertebral morphometry and measure the Cobb angle directly on three-dimensional (3D) computed tomography (CT) images of the spine. [20] Deep learning in spinal disease diagnosis DL algorithms have been employed to diagnose a variety of spinal diseases, such as tumor, [21] infection, [21] osteoporosis, [22] scoliosis, [22] fracture [23] and degenerative disease. [24] For instance, CNNs demonstrated high accuracy in differentiating between normal and stenotic lumbar spine on MRIs.…”
Section: Deep Learning In Spinal Image Recognitionmentioning
confidence: 99%